ANALISIS REAKSI PASAR TERHADAP PENGUMUMAN MERGER DAN AKUISISI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2021 - Agus Sofian, (2022)
Mergers and acquisitions are one of the business strategies used by the company to expand its business, increase growth, and increase the company's competitiveness. This study aims to determine the reaction of the stock market in the Indonesia Stock Exchange to the announcement of mergers and acquisitions. The variables used in this study are stock prices, abnormal returns, and stock trading volume. The sample used in this study was selected using the purpose sampling method, obtained as many as 37 companies listed on the Indonesia Stock Exchange that carried out mergers and acquisitions in 2017-2021. The hypothesis test method in this study uses the Friedman test method with the help of the IBM SPSS program version 25. The results of hypothesis test indicate that the market does not react to the announcement of mergers and acquisitions, this is proved by the absence of significant stock price differences between before and after the announcement of the merger and acquisition. In addition, the abnormal returns between before and after the announcement of mergers and acquisitions are not significantly different. The volume of stock trading also shows that there is no significant difference between before and after the announcements of mergers and acquisitions.